Recent Trends of Poisoning at Tertiary Care Hospital (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Poisoning is a common public health problem worldwide. This prospective study was carried out in Medicine department of Faridpur Medical College Hospital to observe the recent trends of poisoning including demographic distribution, types and outcome of poisoning from 3rd June, 2018 to 2nd December, 2018. Total 517 patients of acute poisoning were included in this study. Among them, 232 (44.9% ) were male and 285 (55.1% ) were female. Most of the patients were married (58.4% ), muslim (93.8%) and they lived in rural area(88.8% ). By occupation, housewives were the maximum (29%) followed by farmers (25.1% ). Most of them were exposed to poisoning in oral route (99.2% )and only (0.8% ) patients were exposed through inhalation. Organophosphorus compound poisoning was the most common type of poisoning (32.9% ) and the death rate associated with OPC poisoning was highest (3.7%). The 2nd most common poisoning was sedative poisoning (17%) followed by commuter poisoning (13.7%), corrosives (10.8%), unknown (6.6%), herbicides (6.2%), mixed drug poisoning (6%), rat killer poisoning (1.9%), Others (4.8%). Age group 1 (10-20 years) was the most vulnerable group (45.6%). According to manner of poisoning, 481 (93%) were exposed to poisoning in suicidal attempt followed by accidental 33(6.4%) and homicidal 3 (0.6%). Familial disharmony was the principal cause of suicidal poisoning (82.5%). Female patient ingest poison with suicidal attempt 267(55.5%) more than male 214 (44.5%).Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(2):85-90